Building resilient industries and entrepreneurship in competitive world: the way forward - Abdul Rahman, Shukran (2018)
This paper outlines the characteristics of a harmonious industries and entrepreneurship society and discusses the roles of HE vis a vis the competitive world. It highlights the interrelated-roles HE should play in the development of resilient industry and entrepreneurship society. The paper recommend a set of synergized guides which are the blend of empirical work and divine source, in promoting resilient society by highlighting the integration of reveled knowledge and Psychology.